Characteristics of Escherichia coli ST131 strains isolated from dogs and cats with urinary tract infections in a teaching hospital in Taiwan - Shu-Xian Lin; Kuang-Sheng Yeh (PLoS ONE, 2026)
Escherichia coli sequence type (ST) 131 is a globally disseminated multidrug-resistant clone that poses a substantial public health threat. This study investigated the prevalence, virulence characteristics, and antimicrobial resistance profiles of ST131 among companion-animal E. coli isolates. A total of 400 E. coli isolates obtained from dogs and cats diagnosed with urinary tract infections at the National Taiwan University Veterinary Hospital between 2011 and 2019 were analyzed. Phylogenetic grouping identified 192 isolates (48.0%) belonging to phylogroup B2, which is strongly associated with ST131. Among these, 26 isolates (13.5%) were confirmed as ST131 by single-nucleotide polymorphism screening and multilocus sequence typing, and 19 isolates were selected for detailed characterization. Virulence gene analysis by multiplex PCR showed that fyuA (100.0%), traT (94.7%), iutA (89.5%), and kpsMT II (84.2%) were the most prevalent genes. Antimicrobial susceptibility testing demonstrated universal susceptibility to meropenem, whereas all isolates were resistant to amoxicillin and ampicillin. Six canine-derived isolates produced extended-spectrum β-lactamases (ESBLs) or AmpC β-lactamases. Among ESBL producers, bla gene groups bla CTX-M-1 , bla CTX-M-9 , and bla TEM were detected, whereas bla CMY-178 was the only AmpC gene identified. Conjugation experiments demonstrated transferability for most bla genes, except bla TEM-102 , bla TEM-12 , and bla CTX-M-55 . Plasmid replicon typing revealed IncF (100%) and IncB/O (69%) as the predominant plasmid groups. Only two O-antigen types, O25b and O16, were detected among ST131 isolates, which carried fimH variants fimH22 , fimH27 , fimH30 , or fimH41 subclones. These findings demonstrate the circulation of virulent and multidrug-resistant ST131 strains in companion animals in Taiwan, highlighting their potential relevance within a One Health context.